Risk factors for breast cancer in young women by oestrogen receptor and progesterone receptor status - McCredie, M R E (Nature Publishing Group, 2003)
We used data from 765 cases and 564 controls in the population-based Australian Breast Cancer Family Study to investigate whether, in women under the age of 40, the profile of risk factors differed between breast cancer subtypes defined by joint oestrogen and progesterone receptor status. As hypothesised, no significant differences were found.